Relationship between DiaSorin Liaison Treponema pallidum antibody indices and confirmatory assay results in the reverse syphilis testing algorithm - Prince, Harry E.; Marlowe, Elizabeth M.; Schwab, Dale A. (Diagnostic microbiology and infectious disease, 2021)
Published studies show that >99% of sera reactive in the reverse syphilis testing algorithm (RSTA) screening assay with an index above an assay-specific threshold confirm as reactive, with either a rapid plasma reagin-reactive (RPRR) or RPR-nonreactive/Treponema pallidum particle agglutination-reactive (TPPAR) result. However, the relationship between screen indices and confirmatory patterns has not been characterized. We thus assessed confirmatory testing results for 577 sera submitted for RSTA testing and a screen-reactive result in the DiaSorin Liaison assay. The median screen index was significantly higher for RPRR samples than TPPAR samples (55.6 versus 10.4), and the proportion with indices >28.3 (median for all 577 samples) was significantly higher for RPRR versus TPPAR samples (82% versus 26%). However, RPRR titers did not significantly correlate with screen indices (R2 = 0.02). These findings demonstrate a significant relationship between RSTA screen indices and confirmatory assay results. The clinical utility of this relationship requires further study.